Pain management of peritonsillar abscess - Choudhury, A Allam; Sultana, Tuhin; Alauddin, M (Bangladesh Journal of Otorhinolaryngology, 2009)
One year cross sectional study was undertaken in 50 patients with peritonsillar abscess to determine the treatment that was most effective in relieving the excruciating pain associated with the condition. The patients were divided into two treatment groups: intravenous antibiotic, and incision and drainage. The effect of treatment over was objectively assessed by serially measuring the distence between upper & lower incisor and by giving the patient water to drink at regular intervals to determine the point at which swallowing was pain-free. The improvement of the mean upper to lower incisor distance 15 minutes after the initial treatment was five per cent in the intravenous antibiotic group and 100 per cent in the incision and drainage group. None of the patients in the intravenous antibiotic group was able to swallow water two hours after the initial treatment. In the same time interval 23 patients (92 per cent) in the incision and drainage group were able to swallow water. The conclusion derived from this study is that incision and drainage is superior to intravenous antibiotic in relieving the pain associated with peritonsillar abscess. Key words: Peritonsillar Abscess, Pain. DOI: 10.3329/bjo.v14i1.3273 Bangladesh J of Otorhinolaryngology 2008; 14(1) : 6-8